Imaging Multidrug Resistance P-glycoprotein Transport Function Using MicroPET with Technetium-94m-Sestamibi - Heather M. Bigott; Julie L. Prior; David R. Piwnica-Worms; Michael J. Welch (Molecular Imaging)
The best characterized mechanism of multidrug resistance (MDR) in cancer involves the MDR1 efflux transporter P-glycoprotein (Pgp). The positron-emitting radiotracer hexakis (2-methoxyisobutylisonitrile)- 94m Tc ( 94m Tc-MIBI) was synthesized and validated in cell transport studies as a substrate for MDR1 Pgp. In vivo small-scale PET imaging and biodistribution studies of mdr1a/1b (−/−) gene deleted and wild-type mice demonstrated the use of 94m Tc-MIBI to detect Pgp function. The reversal effect of a Pgp modulator was shown in tissue distribution studies of KB 3–1 (Pgp-) and KB 8–5 (Pgp+) tumor-bearing nude mice. The current 94m Tc-MIBI experiments parallel previous studies employing 99m Tc-MIBI, showing essentially identical performance of the two technetium radiotracers and providing biological validation of 94m Tc-MIBI for PET imaging of multidrug resistance.